Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XIX: New supplements to the genus Apterolarnaca Gorochov, 2004 - Zhang, Qianwen; Luo, Yehong; Bian, Xun (Zootaxa, 2023)
In this paper, we first provide holotype illustrations of six known species. Then based on new specimens, five new species are described. We also discovered the male sex of Apterolarnaca (Bianigryllacris) quadratus (Li & Liu, 2015), and described and illustrated for the first time. All examined specimens are deposited in Guangxi Normal University.